2001
DOI: 10.1111/j.1348-0421.2001.tb01272.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection and Quantification of Five Periodontopathic Bacteria by Real‐Time PCR

Abstract: Abstract:The quantity of periodontopathic bacteria in plaque samples is an important determinant for understanding the etiologic role of bacteria. The real-time PCR method was used to detect and quantify periodontopathic bacteria, such as Actinobacillus actinomycetemcomitans, Bacteroides forsythus, Porphyromonas gingivalis, Treponema denticola, and Treponema socranskii, in saliva and subgingival plaque samples. There was good agreement between the results of conventional PCR and real-time PCR methods. Using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
114
1
11

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(134 citation statements)
references
References 9 publications
8
114
1
11
Order By: Relevance
“…This finding indicated that the use of saliva as well as subgingival plaque in the analysis of the oral bacterial community is effective. In addition, periodontopathic bacteria such as Actinobacillus actinomycetemcomitans, Tannerella forsythensis (formerly Bacteroides forsythus) (Sakamoto et al, 2002), Porphyromonas gingivalis, Treponema denticola and Treponema socranskii were more frequently detected in saliva than in subgingival plaque samples by the real-time PCR (Sakamoto et al, 2001). These results confirmed those of a previous study (Umeda et al, 1998).…”
Section: Introductionsupporting
confidence: 82%
“…This finding indicated that the use of saliva as well as subgingival plaque in the analysis of the oral bacterial community is effective. In addition, periodontopathic bacteria such as Actinobacillus actinomycetemcomitans, Tannerella forsythensis (formerly Bacteroides forsythus) (Sakamoto et al, 2002), Porphyromonas gingivalis, Treponema denticola and Treponema socranskii were more frequently detected in saliva than in subgingival plaque samples by the real-time PCR (Sakamoto et al, 2001). These results confirmed those of a previous study (Umeda et al, 1998).…”
Section: Introductionsupporting
confidence: 82%
“…The sequences are shown in Table 1. The number of total bacteria was determined using the SYBR GREEN I format, and the primers were designed according to a previously reported method (17). In the PCR reaction to determine the number of total bacteria, 5 µl DNA was reacted in a 20-µl reaction solution containing SYBR Premix Ex Taq (Takara Bio Inc., Kyoto, Japan) and 0.5 µM primers.…”
Section: Quantitative Pcrmentioning
confidence: 99%
“…In particular, real-time PCR is simple, rapid, and useful for detecting uncultured or extremely anaerobic microorganisms. 6 Many studies have reported quantitative changes in bacterial levels related to orthodontic treatment and periodontal pathogens related to oral hygiene during orthodontic treatment. 7,8 However, few studies have investigated quantitative changes in periodontal pathogens after orthodontic treatment, specifically in saliva.…”
Section: Introductionmentioning
confidence: 99%